1996
DOI: 10.1177/153857449603000203
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin Usage for Spinal Cord Protection During Experimental Thoracic Aortic Cross-Clamping

Abstract: The risk of paraplegia associated with thoracic aortic cross-clamping is high even when various methods of spinal cord protection are used. In this study prostacyclin 12 (PGI2) was selected as an agent to reduce the spinal cord injury because of its vasodilator, antiaggregant, and cytoprotective properties.Twelve dogs underwent sixty-minute aortic occlusion. Six dogs received PGI2 whereas the other 6 did not (controls). PG12 administration was started at a rate of 5 ng/kg/minute five minutes before aortic occl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…11 We have also demonstrated that prostacyclin can reduce the risk of spinal cord injury. 3,4 These drugs increase the spinal cord blood flow, whereas sodium nitroprusside used as a vasodilator lowered spinal cord perfusion pressure and increased the risk of neurologic injury. 12 It is our belief that any vasodilator that increases cyclic adenosine monophosphate levels, reduces the incidence of neuro-logical injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 We have also demonstrated that prostacyclin can reduce the risk of spinal cord injury. 3,4 These drugs increase the spinal cord blood flow, whereas sodium nitroprusside used as a vasodilator lowered spinal cord perfusion pressure and increased the risk of neurologic injury. 12 It is our belief that any vasodilator that increases cyclic adenosine monophosphate levels, reduces the incidence of neuro-logical injury.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Various methods such as pharmacological agents and shunt procedures have been used to protect the spinal cord from ischemia but none have been uniformly successful. [3][4][5][6][7] The aim of these techniques is either to increase the spinal cord blood flow or to reduce the risk of ischemia-reperfusion injury. Papaverine has been shown to significantly increase spinal cord blood flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, papaverine was used as a drug to increase the spinal cord blood flow because it reverses the basilar artery spasm induced by subarachnoid hemorrhage (10). We also demonstrated that prostacyclin can reduce the risk of spinal cord injury (4,5). Both of these drugs increase the spinal cord blood flow.…”
Section: • Pmentioning
confidence: 96%